2021
DOI: 10.22212/jekp.v12i2.2237
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Program Bantuan Pangan Nontunai di Kota Yogyakarta

Abstract: Non-Cash Food Assistance (BPNT) aims to help the poor in accessing some of their food. Unfortunately, various obstacles and challenges are still found in the implementation that can potentially reduce the full benefits of BPNT. This research aims to analyze the effectiveness of BPNT implementation in Yogyakarta City as a pilot area. A qualitative approach is used to answer it, supplemented by a variety of primary and secondary data. The primary data comes from a questionnaire based on an e-warong perspective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
0
0
1
Order By: Relevance
“…Namun, program BPNT masih terjadi kendala dalam hal kualitas pangannya. Seperti penyaluran BPNT di Kota Yogyakarta, penerima meminta untuk kualitas beras yang disediakan Perum Bulog perlu ditingkatkan (Izzaty et al, 2021). Padahal kualitas pangan menjadi penting karena hal tersebut akan berdampak bagi kesehatan masyarakat yang mengonsumsi.…”
Section: Gambar 9 Perbandingan Penghasilan Menurut Jenis Pekerjaanunclassified
“…Namun, program BPNT masih terjadi kendala dalam hal kualitas pangannya. Seperti penyaluran BPNT di Kota Yogyakarta, penerima meminta untuk kualitas beras yang disediakan Perum Bulog perlu ditingkatkan (Izzaty et al, 2021). Padahal kualitas pangan menjadi penting karena hal tersebut akan berdampak bagi kesehatan masyarakat yang mengonsumsi.…”
Section: Gambar 9 Perbandingan Penghasilan Menurut Jenis Pekerjaanunclassified
“…Adanya Bantuan Pangan Non Tunai (BPNT) bisa membantu masyarakat miskin dengan memenuhi kebutuhan pokok masyarakat, juga masyarakat bisa memberikan dukungan pada program ini sehingga angka kemiskinan bisa turun ini sejalan dengan penelitian (Angga 2022;Das 2021;Fadlurrohim, Nulhaqim, and Sulastri 2020;Hermawan et al 2021;Hidayat Srihadi Hidayat, Afifuddin 2021;Maghfiroh, Budiarto, and Khairunnisyah 2020;Mufatiroh, Ratnawati, and Ananda Kurniawan 2021;Nabila, Suharso, and Hartanto 2021;Sari, Kusbandrijo, and Murti 2019;Wiyaka and Murti 2019).…”
Section: Pendahuluanunclassified
“…Especially in Indonesia, Non-Cash Food Assistance or basic food programs have long been implemented to help the poor. The results of research by Hermawan et al (2021) which was carried out in the City of Yogyakarta found that the Non-Cash Assistance Program had been running effectively but still needed to improve performance in various aspects. In various regions in Indonesia, the Non-Cash Food Assistance Program or the staple food program is still not on target.…”
Section: Introductionmentioning
confidence: 99%